2017
DOI: 10.1556/2006.6.2017.066
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Parents’ Perceived Self-Efficacy to Manage Children’s Internet Use Scale for parents of adolescents with attention-deficit/hyperactivity disorder

Abstract: Background and aimsThis study developed and validated the Parents’ Perceived Self-Efficacy to Manage Children’s Internet Use Scale (PSMIS) in the parents of children with attention-deficit/hyperactivity disorder (ADHD).MethodsIn total, 231 parents of children with ADHD were invited to complete the PSMIS, followed by the Chen Internet Addiction Scale and the short version of Swanson, Nolan, and Pelham, Version IV Scale – Chinese version for analyzing Internet addiction severity and ADHD symptoms, respectively.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…We used the PSMIS [ 37 ] to measure parents’ self-efficacy in managing adolescent Internet use in the previous month. The scale contained 18 items in four dimensions: safety management (6 items), parental reasoning (4 items), rule-setting practices (4 items), and parental monitoring (4 items).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the PSMIS [ 37 ] to measure parents’ self-efficacy in managing adolescent Internet use in the previous month. The scale contained 18 items in four dimensions: safety management (6 items), parental reasoning (4 items), rule-setting practices (4 items), and parental monitoring (4 items).…”
Section: Methodsmentioning
confidence: 99%
“…Each item was rated on a 7-point Likert scale ranging from 0 (no efficacy at all) to 6 (extremely strong efficacy). The reliability and validity of the PSMIS have been described elsewhere [ 37 ]. The mean scores were calculated.…”
Section: Methodsmentioning
confidence: 99%
“… 1 According to the surge in smartphone ownership, adolescents frequently use smartphones after school, during classes, while eating, and while taking transportation. 2 3 However, problematic internet gaming and internet addiction are becoming increasingly serious problems. 4 Several studies showed that the risk factors for internet gaming disorder (IGD) include social isolation, lower-quality interpersonal relationships, low academic achievement, limited recreational activities, and low self-esteem.…”
Section: Introductionmentioning
confidence: 99%
“…As the closest person to their children, parents who accompany their children during online learning can perceive their health status over time. Hsieh et al (2017) indicated that parents can perceive students' emotional changes in learning. Therefore, parents are more likely to perceive their children's academic stress by perceiving their physical and mental health.…”
Section: Introductionmentioning
confidence: 99%
“…As the closest person to their children, parents who accompany their children during online learning can perceive their health status over time. Hsieh et al. (2017) indicated that parents can perceive students' emotional changes in learning.…”
Section: Introductionmentioning
confidence: 99%